2005
DOI: 10.1074/jbc.m500393200
|View full text |Cite
|
Sign up to set email alerts
|

The Global Transcriptional Response of Escherichia coli to Induced σ32 Protein Involves σ32 Regulon Activation Followed by Inactivation and Degradation of σ32 in Vivo

Abstract: Escherichia coli core DNA-dependent RNA polymerase consists of four different subunits and has the composition ␣ 2 ␤␤Ј. Core RNA polymerase (E) together with a factor constitutes a holoenzyme complex (E) (1, 2). The holoenzyme complex is able to initiate transcription at specific DNA sequences termed promoters. Since the discovery of 70 36 years ago, numerous factors have been described in E. coli and other prokaryotic organisms (3-7). The seven known E. coli factors are 70 , 54 , 32 , S , F , E , and fecI .Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
145
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 62 publications
(153 reference statements)
15
145
1
2
Order By: Relevance
“…These genes encode the heatshock proteins Hsp40, HptG, DnaK, DnaJ, GroES and GroEL, which were all induced after heat stress as well. The previous studies of the s 32 regulon in E. coli, V. cholerae and N. gonorrhoeae identified these genes also (Gunesekere et al, 2006;Nonaka et al, 2006;Slamti et al, 2007;Zhao et al, 2005), demonstrating common features of RpoH regulation in different species. However, the number of genes identified in F. tularensis was unexpectedly low when compared with other bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…These genes encode the heatshock proteins Hsp40, HptG, DnaK, DnaJ, GroES and GroEL, which were all induced after heat stress as well. The previous studies of the s 32 regulon in E. coli, V. cholerae and N. gonorrhoeae identified these genes also (Gunesekere et al, 2006;Nonaka et al, 2006;Slamti et al, 2007;Zhao et al, 2005), demonstrating common features of RpoH regulation in different species. However, the number of genes identified in F. tularensis was unexpectedly low when compared with other bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we verified that together with the induction of cpxP occurred a high number of transcriptionally modified genes involved in cell wall biogenesis and in protein folding, including genes encoding heat-shock proteins (ibpAB, hslJ, htpX), chaperones (dnaJ, htpG, clpB) and proteases (ftsH) ( Supplementary Table S1), mainly under anaerobic conditions. These genes are under the control of rpoH (s 32 ) (Zhao et al, 2005), a gene that was also found to be upregulated by CORM-2 under anaerobic conditions. The study of the growth behaviour of the DcpxP mutant revealed that this strain is approximately 35 % more sensitive to CORM-2 than the parental strain, but only under anaerobic conditions (Fig.…”
Section: Phenotypic Analysis Of E Coli Regulators Induced By Corm-2mentioning
confidence: 99%
“…Several global approaches have been utilized in E. coli to identify genes under 32 control. Both two-dimensional protein gels (Lemaux et al 1978) and global transcriptional approaches have identified genes induced after transfer to high temperature (Chuang et al 1993b;Richmond et al 1999) or after overexpression of 32 (Zhao et al 2005); however, there has been no systematic determination of whether these induced genes are directly expressed from 32 -dependent promoters. The few cases where the functions of 32 -dependent genes were identified indicates the importance of this determination: Hsp33, a widely conserved hsp, is a redox activated chaperone (Jakob et al 1999), thereby providing the first identification of a chaperone of this type, and FtsJ was shown to be a methyltransferase whose substrate is 23S RNA, revealing an unexpected link between the HSR and RNA (Bugl et al 2000).…”
mentioning
confidence: 99%
“…We also tested seven previously proposed 32 promoters located upstream of genes that were not significantly induced on our arrays and detected no 32 -dependent transcripts (Table 1C). Finally, neither 5ЈRACE nor in vitro transcription identified functional promoters for three of the 32 promoters proposed by Zhao et al (2005) (ldhA, macB, and ybbN; Table 1B) based on electrophoretic mobility gel shift by stream of sequences not present on our arrays (Table 1C) comprise a total of 51 promoters that drive the expression of 49 TUs. The sequence logos of the conserved sequence motifs upstream of the 50 chromosomal 32 promoters (note repE is on the F factor) together with their information content are displayed in Figure 4A.…”
mentioning
confidence: 99%